Identifikasi dan Karakterisasi Senyawa Aktif Ekstrak Daun Murbei (Morus alba L.) - Subehan Lallo; Hamdayani L A; Besse Hardianti; Rizki Asmawati Bahar (STIFA Makassar, 2017)
Mulberry (Morus alba L.) is commonly use in the cultivation of silkworms and medicinal plants in Indonesia. Traditionally, the leave are used to decrease arterial blood pressure. This study has been carried out the identification and characterization of compounds that isolated from the M. alba leaves collected from South Sulawesi. Extraction was done by maceration of their leaves using ethanol 0%, separation and purification using chromatography method. The results of the stationary phase column chromatography with silica gel with the mobile phase n-hexane:ethyl acetate in a gradient system obtained fractions with the fraction showed clear spot at TLC was continued for isolation. The isolated compound was analyzed with IR and UV-VIS spectrophotometry. Analysis of IR spectrum indicated the presence of an O-H (2285 to 2385 cm-1), C-H (2854 to 2954 cm-1) and the C=C (1521 to 1577 cm-1), these isolates indicate the presence of flavanoid compounds and their functional group at wavenumber 1336; 3421; and 968-1273 cm-1 indicated the presence of C-N; N-H; and C-O functional groups, respectively. These data also indicated the possibility of alkaloids. In addition characterization with UV sprectrum showed absorption at a wavelength of 239 and 413 nm, they indicated the presence of flavonoid group.